The Education and Social Justice: A Phenomenological Review of Educational Access Disparities in Developing and Developed Countries - Judijanto, Loso; Prananda, Gingga; Naofal, Muhammad; Ayu, Dwi Hadita; Hendra, Muhammad; Handayani , Linda (The Future of Education Journal, 2025)
This study aims to analyze the educational access disparity between developing and developed countries, focusing on the causes, impacts, and policies implemented. The methodology used is a literature review, examining various sources and previous studies related to educational disparities in both types of countries. The findings indicate that developing countries face greater disparities due to limited educational infrastructure and a lack of trained human resources. Meanwhile, developed countries, despite having better infrastructure, experience disparities mainly caused by socio-economic factors, such as differences in educational access for minority groups and children from poor families. This study concludes that to reduce educational disparities, more inclusive and equitable policies are needed, along with the use of educational technology that can expand access to education in remote areas and among disadvantaged groups.